2022
DOI: 10.22159/ijap.2022.v14s5.26
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and Antioxidant Activities of Aqueous Extract Moringa Oleifera Leaves

Abstract: Objective: To investigate the neuroprotective and antioxidant effects of leaves aqueous extract Moringa oleifera (MW) in chronic stress mouse models. Methods: Water immersion and stress restraint for 16 d to obtain a chronic stress model animal. Moringa extract flour dissolved in Aquades, dose 800 mg/kg for 23 d, for chronic Stress+MOW group. Fluoxetine in aquades at a dose of 18 mg/kg BW for 23 d for chronic stress group+Fluoxetine. Aquades were given to normal mice (group N), and mice under chronic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…BDNF and TrkB are highly associated with senescence because BDNF has a high affinity for TrkB's primary ligand [ 41 ]. However, our previous study showed that MOE can increase the expression of BDNF mRNA in a chronic stress model [ 42 ]. This discrepancy could be attributed to the lower dose administered in this study compared with the previous one.…”
Section: Resultsmentioning
confidence: 99%
“…BDNF and TrkB are highly associated with senescence because BDNF has a high affinity for TrkB's primary ligand [ 41 ]. However, our previous study showed that MOE can increase the expression of BDNF mRNA in a chronic stress model [ 42 ]. This discrepancy could be attributed to the lower dose administered in this study compared with the previous one.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained crude extract was lyophilized and stored in airtight container. [2][3][4] Test Animals (AKRGCP/Pheuc/2018-2) The Experiment was carried out in A.K.R.G College of Pharmacy, Nallajerla 534-112, and East Godavari district. A.P, and approved by IAEC viz., Ref.…”
Section: Introductionmentioning
confidence: 99%